2009
DOI: 10.1592/phco.29.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Patients with Heart Failure: Clinical Implications and Management

Abstract: Mortality and morbidity rates remain high in patients with heart failure despite advances in medical therapy. Heart failure can also significantly worsen quality of life. Attention has been paid to evaluating the effects of psychological disease in patients with heart failure. Depression rates are higher in patients with heart failure than in the general population. Depression has been associated with worse outcomes in patients with heart failure. Those at highest risk for depression include patients with impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 114 publications
0
20
0
Order By: Relevance
“…Additionally, the results of the present study showed a positive association between depression and migraine and heart condition comorbidities. Several studies reported the relationship of depression with cardiovascular disease [27,28], which is well known to be correlated with RA [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results of the present study showed a positive association between depression and migraine and heart condition comorbidities. Several studies reported the relationship of depression with cardiovascular disease [27,28], which is well known to be correlated with RA [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The primary mechanism of action of SSRIs results in increased serotonin circulation by blocking presynaptic serotonin receptors. This results in a downregulation of the actual receptors, sustaining the level of circulating serotonin [30,32]. This effect has been shown to improve mood in patients with depression, decreasing the prevalence of clinical depression.…”
Section: Major Clinical Trials For Post-myocardial Infarction Depressionmentioning
confidence: 99%
“…possibly, either patients with ACs or patients without the syndrome had greater experience with cardiac symptoms, a situation that could have influenced the different rates of depression in the 2 groups, because chronic heart disease is associated with greater rates of depression than is newonset disease. 33 We did not assess the occurrence of previous cardiac events or the duration of CHD in our sample. Thus, we cannot examine the influence of living with CHD on rates of depression in our patients.…”
Section: Resultsmentioning
confidence: 99%